Optical Density of Subretinal Fluid as a Predictive Biomarker for Eyes With Chronic Central Serous Retinopathy Treated With Eplerenone. (January 2018) - Joshi, Nisarg P.; Adam, Murtaza K.; Samara, Wasim A.; Shahlaee, Abtin; Rahimy, Ehsan; Aderman, Christopher M.; Hsu, Jason; Fineman, Mitchell S.; Garg, Sunir J.
Purpose: To investigate how the optical density ratio (ODR) of subretinal fluid (SRF) obtained by optical coherence tomography (OCT) in eyes with chronic central serous retinopathy (CSR), defined as symptoms >3 months, treated with eplerenone correlates with treatment response and visual outcomes. Methods: This retrospective, single-center observational study included patients with chronic CSR treated with eplerenone who had at least 6 weeks of follow-up. Eyes with poor-quality OCT scans, shallow SRF precluding sampling of optical density (OD), and macular pathology other than CSR were excluded. Optical density of the vitreous and SRF was measured using ImageJ and used to calculate ODR (ODR = ODSRF /ODVIT ). Peak SRF height, foveal SRF height, central macular thickness (CMT), and Snellen visual acuity (VA) were measured. The Mann-Whitney U test was used to compare continuous variables. Pearson correlation coefficient was used to determine the statistical significance of applied linear regressions. Results: Twenty-three eyes of 23 patients met the inclusion criteria. Six (26%) eyes had complete resolution of foveal SRF (resolvers) with eplerenone treatment, and the remainder of patients had worsening or incomplete resolution (nonresolvers). Resolvers had significantly lower baseline logarithm of the minimum angle of resolution (logMAR) VA ( P < .01) than nonresolvers. There was a positive linear correlation between ODR and logMAR VA at baseline ( R 2 = 0.208; P = .03) and follow-up ( R 2 = 0.206; P = .03). A significant correlation between ODR and percentage change in CMT was found ( R 2 = 0.263; P = .01). Linear correlations were not found between ODR and age, peak SRF height, and foveal SRF height (all P > .125). Conclusion: Lower baseline ODR was associated with improved percentage change in CMT and VA in patients treated with eplerenone for chronic CSR. Optical density ratio may represent a novel prognostic biomarker that may help determine which eyes with chronic CSR may respond better to eplerenone.